Development and validation of nomogram including mutations in angiogenesis-related genes as risk factors for HCC patients treated with TACE - Wanqing Shen; Zhi Li; Jinyi Huang; Guixiong Zhang; Yiyang Tang; Wenzhe Fan; Jiaping Li (Translational Oncology)
Background: As a vascular-rich solid tumor, hepatocellular carcinoma (HCC) patients with poor transarterial chemoembolization (TACE) respone or treatment failure may correlate with tumor angiogenesis in residual disease. However, their relationship remains unclear. This study aims to explore the relationship between angiogenesis-related genes and TACE failure in patients with HCC and to develop a predictive model for assessing treatment outcomes. Materials and Methods: Somatic mutation profiles of 165 patients with HCC treated with TACE were analyzed using whole-exome sequencing (WES). Multivariate Cox regression analysis was performed to calculate the genetic risk score (GRS) for angiogenesis-related gene mutations. The participants were randomly divided into training and validation groups. In the training set, independent prognostic factors of TACE-treated patients with HCC were screened using univariate Cox-LASSO-stepwise Cox regression, and a nomogram was established and evaluated using the receiver operating characteristic curve, calibration curve, and decision curve analysis of the two sets. Results: Among 165 patients, significant genetic alterations were identified, with TP53 being the most frequently mutated gene. Mutations in FGFR4, MST1R, and RECK were associated with the treatment efficacy of patients receiving TACE treatment, and the constructed GRS was associated with poor prognosis. Furthermore, AFP, ALT, AST, PLR, PD-L1 immune drug treatment, and GRS were confirmed as independent factors affecting the prognosis of patients with HCC treated with TACE. A nomogram was constructed, which demonstrated excellent discrimination, calibration, and clinical benefits in both the training and validation sets. Conclusion: These findings highlight the critical role of angiogenesis-related genes in predicting TACE outcomes in patients with HCC and indicate that the developed prognostic model and nomogram can serve as valuable tools to predict prognosis based on the GRS of angiogenesis-associated gene mutations. Implications for Practice: Our findings highlight the critical role of angiogenesis-related genes in predicting TACE outcomes in HCC patients. The developed prognostic model and nomogram can serve as valuable tools for clinicians, enhancing decision-making and treatment strategies for HCC management.